Numerical Investigation of Enhanced Heat Transfer with Micro Pin Fins in Heat Exchangers - Qin Zhou; Hongyan Wang; Fuyuan Wu; Shengfei Liu; Huafeng Wei; Guoqing Hu (Micromachines)
Pin-fin and flat-tube heat exchangers (PFFTHXs) offer a promising alternative to traditional louvered-fin and flat-tube heat exchangers (LFFTHXs), especially when used as evaporators. The streamlined structure of pin fins helps to effectively remove condensate and defrost water. In this study, we conducted a numerical analysis of 60 different pin-fin configurations across three pin diameters to enhance heat transfer in PFFTHXs. Our investigation focused on how pin pitch affects both airflow and heat transfer efficiency. The results show that a closer pin pitch increases both the heat transfer rate per unit area and the pressure drop for a given airflow velocity. We evaluated the overall performance of these configurations using the heat transfer rate per unit frontal area obtained at equivalent fan power levels. The analysis identified optimal configurations for each pin diameter, with the 0.2 mm diameter configuration demonstrating the highest heat transfer efficiency—this was on par with louvered fins but used fewer resources. This makes it an ideal choice for evaporative applications in PFFTHXs.